A Interpelação de Althusser no Teatro do Direito Burguês - Fialho, Noêmia Amélia Silveira (2024)
In 1970 Althusser presents his theory of Ideology and Ideological State Apparatuses as an ongoing research that aims to study the reproduction of bourgeois society in the twentieth century. To emphasize its material existence, the philosopher maintains that ideology challenges individuals in subjects. It presents the questioning of a policeman to any individual on the street as a theoretical scene precisely with the aim of illustrating the concrete functioning of ideology. Our research aims to study the figure of interpellation, on the one hand, deepening its metaphorical value through the Althusserian theorization of the materialist theater, and, on the other, questioning its critical force before the concepts of representation and subject of law based on the ideological dimension of the "Political State Apparatus". This study has as its firm point the centrality that Althusser recognizes to the legal ideology for the dominant ideology in bourgeois societies. This is because it is on the basis of bourgeois law that the subject embodies the determination of exchange value and has the ideals of equality and freedom grounded on the basis of exchange relations. The notions derived from the legal ideology also support the production of the political State Apparatus, as Althusser describes it in the 1976 Notes on the ISA, and support its reproduction, since political representation is legitimized because those represented are considered free and equal to elect their representatives (the ideological dimension of the social pact). Thus, citizens are, ultimately, considered authors of the acts practiced by the one who represents them (author-actor dialectic).